A Incubadora Social da UFSM: uma proposta metodológica para promover impacto social - Weinitschke, Elisandra Della Flora (2021)
This study aimed to develop an incubation methodology in accordance with the objectives and characteristics of the UFSM Social Incubator, considering the need for this tool to instruct, guide project coordinators, work team and, mainly, contribute to the incubated projects can develop their proposals better and obtain better results. For this, bibliographic and documentary data were collected, as well as the application of interviews in social incubators linked to the ITCP network, in order to provide the necessary support for the methodological construction. The survey revealed that, of the ten incubators participating in this study, most seek to follow the incubation stages, but not all determine a time limit, focusing on the development and sustainability of the incubated enterprises. Few adopt indicators to assess their performance or that of their incubated companies and the topic of Social Impact Business is also little discussed. Those that have a clear incubation method are conducted by multidisciplinary teams that are more experienced in the work developed with groups in social vulnerability. There are still many challenges surrounding social incubation, from problems such as the high turnover of the people involved to the lack of financial resources and investment to implement and maintain their projects. To improve the methodology of incubators, further research is suggested on social technologies, indicators and businesses that can impact the target audience of a social incubator, because, despite the intention and reasons presented, most of these incubators are still unable to develop such themes.